Kemampuan Pembuktian Matematika Siswa Sma Pada Materi Trigonometri Menggunakan Pembelajaran Berbasis Bukti Berbantuan Software Geogebra - Aprilianty, Dhea Riski; Meryansumayeka, Meryansumayeka; Scristia, Scristia; Yusuf, Muhammad (SJME (Supremum Journal of Mathematics Education), 2024)
NCTM revealed that one of the five process standards that learners must have is reasoning and evidence. One of the mathematical topics that is loaded with mathematical proof is trigonometry. Given the enormous contribution of computers to mathematics lessons, one of the media that can be used in this material is the geogebra media system. The purpose of the study was to describe the ability of high school students to prove mathematics of trigonometric material using evidence-based learning assisted by geogebra software. The subject of his research was a grade XI student of SMA Srijaya Negara Palembang. This type of research is descriptive with qualitative methods using research instruments including written tests and interviews. The results of research that have been conducted show that students' mathematical proof ability is classified as medium category. Students have raised indicators of mathematical proof ability including identifying data with a percentage of 77.5%, stating the relationship between data with conclusions with a percentage of 87.5%, using premises, definitions, or theorems with a percentage of 56.67%, and constructing proofs using geogebra software with a percentage of 30%.